Implementasi Implementasi Kebijakan Publik Dengan Konsep Good Governance Dalam Meningkatkan Pemasaran Potensi Produk Domestik Program Gerai Maritim Dan Umkm - Karjono Karjono; Evyana Diah Kusumawati; Karmanis Karmanis (Departemen Teknik Kelautan Universitas Hasanuddin, 2023)
This study aims to determine the existence of public policy uncertainty in the concept of good governance which can be a source of non-compliance by people to law or public policy, understanding of competence and commitment to understanding the marketing of domestic products is still low and the facilities and infrastructure in increasing the marketing potential of domestic products are less supportive. The population in this study were MSME industry players and 250 respondents. Data collection was carried out using the questionnaire method via Google form and direct interviews. The test of this instrument was carried out on 50 industrial players in the 3 tp area. The methodology used uses a qualitative approach where data collection techniques use observation techniques (observations), literature studies and interviews (interviews). Analysis of the data used is to use a form of qualitative descriptive method. The observation results obtained are the ability to implement public services in carrying out and serving to provide services to help the community according to what is promised in an appropriate and reliable manner and the reliability of employees in providing services greatly assists the community in providing the promised services, accurately and as expected. The third dimension is Responsiveness ( responsiveness).